2017
DOI: 10.1039/c7ob01534h
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed regioselective C–H halogenation of quinazolinones and benzoxazinones

Abstract: A Pd-catalyzed ortho-selective halogenation of benzoxazinone and quinazolinone scaffolds has been described employing N-halosuccinimide as both a halogen source and an oxidant reagent via C-H bond activation. This transformation shows high chemo- and regioselectivities and demonstrates a broad range of benzoxazinone and quinazolinone substrates with different functional groups and has been scaled up to the gram level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…[24] Other oxidants such as K 2 S 2 O 8 , H 2 O 2 , AgOAc and Cu(OAc) 2 did not promote the desired reaction (Table 1, entries 7- 10). Other catalysts including Cu(OAc) 2 , PdCl 2 , Ru(p-cymene)Cl 2 , Ru(COD)Cl 2 , and Co(OAc) 2 were also ineffective under the present conditions (Table 1, entries [15][16][17][18][19]. Additionally, the increase in the mount of TBHP to four equivalents has resulted in a yield increase of up to 52 % (Table 1, entry 12).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…[24] Other oxidants such as K 2 S 2 O 8 , H 2 O 2 , AgOAc and Cu(OAc) 2 did not promote the desired reaction (Table 1, entries 7- 10). Other catalysts including Cu(OAc) 2 , PdCl 2 , Ru(p-cymene)Cl 2 , Ru(COD)Cl 2 , and Co(OAc) 2 were also ineffective under the present conditions (Table 1, entries [15][16][17][18][19]. Additionally, the increase in the mount of TBHP to four equivalents has resulted in a yield increase of up to 52 % (Table 1, entry 12).…”
Section: Resultsmentioning
confidence: 95%
“…In the absence of either Pd(OAc) 2 or TBHP, no product was observed, indicating that Pd(OAc) 2 and TBHP are indispensable ingredients for the CDC/annulation reaction (Table 1, entries 6 and 14). Other catalysts including Cu(OAc) 2 , PdCl 2 , Ru(p-cymene)Cl 2 , Ru(COD)Cl 2 , and Co(OAc) 2 were also ineffective under the present conditions (Table 1, entries [15][16][17][18][19]. It was found that the yield could be remarkably improved by increasing the catalyst loading as an isolated yield of 71 % for the product was obtained in the presence of 10 mol-% of Pd(OAc) 2 (Table 1, entry 20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates with electron‐donating substituent ( p ‐Me) or electron‐withdrawing substituents ( p ‐Cl and p ‐NO 2 ) afforded corresponding acyloxylated products in moderate to good yields (Table , entries 9–11). The electron‐donating substituent ( p ‐Me) led to the higher yield than electron‐withdrawing substituents ( p ‐Cl and p ‐NO 2 ) which could be ascribed to the electrophilic acyloxylation C–H activation to construct a carbon–palladium bond . Acetoxylation of N ‐arylcarbamate with a chloro at meta ‐position afforded product ( 3 l ) in good yield (Table , entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…As the next diversification pathway, we set out to investigate C−H halogenation. There is a previous reported transition‐metal catalyzed ortho‐C–H halogenation of benzoxazinone scaffold, however it was limited to the acidic reaction medium which caused oxazinone ring hydrolysis to open, in addition the dihalogenated product was the major product in the chlorination and iodination of benzoxazinones, in any case, and it was not an ideal condition to challenge the instability of benzoxazinones. We report here that Pd(II)/AgNO 3 catalysts system in conjunction with electrophilic halogenating reagents N ‐halosuccinimides (NBS, NIS) promote the ligand‐directed conversion of arene C−H bonds into carbon‐halogen bonds.…”
Section: Resultsmentioning
confidence: 99%